Changes in the Style and Contents of Abstracts from The Journal of Consulting and Clinical Psychology between the 1960s and the 2010s - Di Feo, Gian; Whissell, Cynthia (Advances in Social Sciences Research Journal, 2020)
This study was conducted to examine changes in the style and content of abstracts from the Journal of Consulting and Clinical Psychology across time. Characteristics examined were word commonness, word activation, word pleasantness, sentence length, abstract length, mentions of inferential statistics and mentions of drugs (both street drugs and pharmaceuticals). Abstracts (N=510) were downloaded from volumes published before the wide introduction of computers (1968-9) and from those published in more current years (2016-17). Scores for word pleasantness and word activation were assessed with the Dictionary of Affect in Language. Word commonness was scored in comparison to a corpus of everyday English, and sentence length and abstract length were measured in terms of number of words. There were several strong and significant differences between abstracts from the pre-computer era and those from the 21st century, including greater length, more mentions of inferential statistics and more mentions of drugs in the later time period. A stepwise discriminant function analysis was able to correctly predict the origin (early or pre-computer versus 21st century) of 98% of the abstracts on the basis of the characteristics measured (canonical correlation=.89).